Pengaruh Kecemasan Ujian terhadap Prestasi Belajar Siswa SMK - Jacinda Alline Yoriana Putri; Athaya Wahyu Garjita (MASALIQ, 2026)
Although the influence of test anxiety on academic achievement has been widely examined, the dynamics of this relationship within the context of vocational education (Sekolah Menengah Kejuruan, SMK) in Indonesia remain relatively underexplored. This study aimed to analyze the effect of test anxiety on the academic achievement of SMK students by taking into account the specific characteristics of vocational education. A quantitative approach with a correlational design was employed, involving 140 SMK students selected through cluster random sampling. Data were collected using 4-point Likert-scale questionnaires that had been tested for reliability (Cronbach’s alpha for test anxiety = 0.888; for academic achievement = 0.915) and were analyzed using simple linear regression. The results showed a significant positive relationship between test anxiety and academic achievement (r = 0.297; p < 0.05), with a contribution of 8.8% (R² = 0.088), indicating that higher levels of test anxiety are associated with higher academic achievement in this context. These findings contribute to the development of facilitating versus debilitating anxiety theory in educational psychology and extend understanding of the role of academic anxiety in vocational education settings. The study concludes that a differential approach is essential for understanding test anxiety in SMK and encourages educators and school counselors to develop guidance programs that not only focus on reducing anxiety but also on managing it as productive learning energy. The implications of this research include theoretical contributions to the vocational educational psychology literature and practical implications for schools, teachers, and counselors in designing contextual interventions, while also opening avenues for further studies on the role of mediating variables such as vocational self-efficacy and SMK-specific coping strategies in the relationship between anxiety and academic achievement.